Quality assurance of post-graduate education: The case of CAPES, the Brazilian Agency for Support and Evaluation of Graduate Education - Jorge Almeida Guimarães; Elenara Chaves Edler de Almeida (Laureate Education Inc, 2012)
CAPES Foundation, The Brazilian Agency for Support and Evaluation of Graduate Education, was created in July 11th, 1951, some few years after the end of World War II, by the initiative of Anísio Teixeira, a pioneer Brazilian educator. At the same time, Alvaro Alberto, another open mind leader pioneer created CNPq, The Brazilian National Research Council. CAPES is linked to the Ministry of Education, and CNPq to the Ministry of Science, Technology and Innovation. Since its creation, CAPES has been responsible for the evaluation and financial support of graduate courses at master and doctorate levels, covering the entire Brazilian graduate system including both public and private institutions. The evaluation procedures consist of critical analysis of annual reports of each course and their re-evaluation every third year. The systematic process includes the recognition and approval of new courses proposed by the universities and research centers. A national plan, designed to establish and support training and development of human resources for strengthening science and technology activities in Brazil, was initiated six decades ago. This plan, named PNPG, can be viewed today as a successful program in terms of the significance of its general output. During this period, this program has been consolidated and is functioning only in the departments or other subdivisions of public or private universities and research centers that are officially accredited to offer degrees at one (Master's) or both (Master's and Ph.D.) levels. Since its beginning, in 1951, a substantial investment has been applied to develop this plan. This investment has been worthwhile since S&T activities were institutionalized; many scientific and technological achievements have been made. To reach such advances the existence of an effective system based on a group of multi-funding agencies was an essential additional factor for the attained advances. Highlights of these advances have been stressed out before by a report in the Science journal as "Research in Latin America" (Guimarães, 1995). In this work we present and discuss the current data and status of the Brazilian venture for developing human resources and for the formation of an active community dedicated to Science and Technology (S & T), also giving a general vision of its importance for the present and future development of the country. DOI: 10.18870/hlrc.v2i3.78